Prevalence trends of transfusion-transmitted infections at a tertiary private hospital blood bank in Uganda: a retrospective 6-year review (2017–2022) - Andrew Marvin Kanyike; Frank Kakuba; Posiano Mayambala; Racheal Nalunkuma; Rachael Mukisa Nakandi; Yusuf Mulumba; Edith Namulema; Simon Peter Nsingo; Robinson Ssebuufu (BMC Infectious Diseases)
Abstract Background Blood transfusion is a life-saving medical intervention that can transmit transfusion-transmitted infections (TTIs). In Uganda, prevalent infections in the general population may increase the risk of TTIs. This study determined the trends in seroprevalence of TTIs, including the Human Immunodeficiency Virus (HIV), Hepatitis B Virus (HBV), Hepatitis C Virus (HCV), and syphilis among blood donations over a 6-year period at a tertiary hospital blood bank in Uganda. Methods This was a retrospective cross-sectional study utilizing data from Mengo Hospital Rotary Blood Bank in central Uganda. Data was accessed through the central electronic system of Uganda Blood Transfusion Services for January 2017 to December 2022. Data was analyzed using STATA version 16.0. Descriptive statistics and time trend analysis were performed. A p-value < 0.05 was considered statistically significant. Results We analyzed 24,547 blood donations, the majority of which were male donors (18,525, 75.5%) within the age group of 25–40 years (9737, 39.7%) and of Blood group O (12,509, 51.0%). The overall prevalence of TTIs was 8.7% (2,142) and significantly higher among males (8.9%, p < 0.001) and those over 40 years (10.7%, p < 0.01). Syphilis had the highest prevalence at 3.0%, followed by HBV (2.8%), HCV (1.7%), and HIV (1.3%). Co-infections were observed in 0.6% (136) of the donors, with the most common being HBV and syphilis (33, 0.1%). The prevalence trends of TTIs analysed among new donations decreased from 13.7% in 2017 to 8.9% in 2022 (p = 0.124). Only HCV showed a statistically significant variation, decreasing from 5.2% in 2017 to 1.7% in 2022 (p = 0.009). Conclusion There is a decreasing trend of TTIs among blood donors in Central Uganda, although the prevalence of HBV and Syphilis remains high. Additional public health interventions to decrease TTI rates in the general population may increase the safety of blood transfusions.